Mafqūd and fasakh in the writings of Muslim jurists and provisions of Malaysian federal territory Islamic family law: the case of MH 370 missing plane - Mahmud, Mek Wok; Mokhtar, Siti Zulaikha (IIUM Press, International Islamic University Malaysia, 2017)
In Islam, there are various forms of dissolution of marriages thatare permitted to avoid the greater evil which may result from their continuance.Wives are granted the right to dissolve a marriage in order to protect theirrights, particularly in the case missing husbands, either alive or dead. This isknown as mafqūd, or missing person. Therefore, the objective of this study isto discuss the concept of fasakh and mafqūd in accordance with the views ofMuslim jurists and the provisions of Islamic family law in Malaysia. This paperalso aims to analyse both those views in the context of the MH 370 incident.This study uses the qualitative method, by collecting data obtained by meansof information gathering within the resources of the library and authoritativewebsites. From the study, it is shown that the wife can apply for divorce on thebasis of fasakh when it is diffi cult to prove the status of a missing husband.In other words, rulings applicable to fasakh can be activated in the case ofmafqūd. Further discussions are expected to fi nd the best period of presumptionof death, since it is based on ijtihād or the discretion of lawmakers.